Structure–Activity Relationship Study of Xanthoxyline and Related Small Methyl Ketone Herbicides - Warot Chotpatiwetchkul; Nawasit Chotsaeng; Chamroon Laosinwattana; Patchanee Charoenying (ACS Omega, 2022)
) were found to be the most active methyl ketones that highly suppressed plant growth at low concentrations. The molecular docking on the 4-hydroxyphenylpyruvate dioxygenase (HPPD) enzyme indicated that carbonyl, aromatic, and azaindole were key interactions of HPPD inhibitors. This finding would be useful for the development of small ketone herbicides.
Keywords: Allelopathy and phytotoxic interactions; Weed Control and Herbicide Applications; Fungal Plant Pathogen Control